Study on effect of gas-liquid two phase physical feature on slug flow in microchannels - Wang, Lin lin (Frontiers in Physics, 2023)
At present, there are relatively few studies on the slug flow generation mode obtained by exchanging gas-liquid two-phase inlets. In this study, an experimental system combining microfluidic devices and high-speed cameras was used to study the effects of gas-liquid two-phase flow rate, liquid physical parameters, etc., On the characteristic length, generation period and other generation characteristics of slug flow, and dimensionless analysis was conducted to investigate the main factors affecting the characteristic length of gas slug. Results show that 1) when the gas flow rate affects the aeroelastic generation characteristics, the aeroelastic characteristic length increases from 443 μm when the gas flow rate increases changes to 657 μm. The generation period decreases rapidly at first and then the change amplitude slows down. The maximum value of aeroelastic generation frequency is 217 s-1; 2) when studying the effect of different liquid flow rates, increasing the liquid flow rate, the characteristic length of the gas bomb gradually decreases, and the generation period of the gas bomb gradually increases. Aeroelastic characteristic length from 770 μm changes to 378 μm. The range of aeroelastic generation cycle is 4–13.4 ms, and the maximum value of aeroelastic generation frequency is 250 s-1; 3) there is a functional relationship between the ratio of aeroelastic characteristic length to channel size L/d and dimensionless gas-liquid flow ratio Q*, Reynolds number Re, Weber number We: Ld=3.677Q*0.58/Re0.11.